PHYTOTHERAPY – HISTORY AND MODERN USE, EXAMPLES OF APPLICATION IN TREATMENT AND EVERYDAY PRODUCTS - Betyna, Monika; Zieliński, Ewa; Zieliński, Maciej; Motylewski, Bernard; Skalski, Dariusz; Brzoskowska, Karolina (Rehabilitation and Recreation, 2020)
Since the beginning of human race, people have used plants as the source of nourishment. Plants are made of proteins, fatty acids and carbohydrates; they contain mineral salts and other kinds of substances such as vitamins. All of the plant compounds are well known to modern science due to technology development and possibility of performing the experiments. However, our accentors could only depend on good luck and observe themselves after use of unknown plant. The knowledge about positive effects after the usage of plant extracts or their consumption were cherished and passed down to next generations. The prescriptions for home-made remedies for rheumatism, different kinds of pain, wounds etc. were always present in people’s life next to plant use in food preparation as spice or medical tinctures. There are certain experiments which showed that plants are very complex organisms. After many years of scientific research, it has been finally discovered what is responsible for making some plants beneficial for human and animal health or dangerous and toxic in other cases. These days, biochemical characters of plant properties do not pose any secret to people who are conscious of the advantages resulting from using them every day. Particularly every cosmetic product contains some secondary metabolites or plant extracts, which provide certain results in everyday body care. When it comes to night creams, certain chemical peelings and face gels plant enzymes should be mentioned. The positive activity of these creams is connected with skin regeneration processes. Flaking is obstructed by the enzymes which are able to degrade dead skin cells. This process may cause new cells’ activation, which will replace dead skin cells. Such a reaction triggered by enzymes is used in treatment of scars, as well as in the prevention of skin aging. The effectiveness of the herbal therapy is found in substances high in biological activities. Herbs and their products of metabolism can be used in medical treatment of numerous conditions such as indigestion disorders starting from malnutrition and ending with obesity. In case of cardiac failure the most important remedies are heart medicaments.